The Relationship Between the Pediatric Nurses’ Knowledge Levels on Preventing Ventilator-Associated Pneumonia and Job Satisfaction - YAVAŞ ÇELİK, Melike and OZTURK COPUR, Ebru and ELMAOĞLU, Erhan (Göbeklitepe Medical Science Journal, 2021)
Introduction: Ventilator-associated pneumonia (VAP); It is defined as pneumonia that occurs at least 48 hours after the patient starts to receive respiratory support on the mechanical ventilator and absent before the patient starts to receive respiratory support.. VAP ranks second among the most common nosocomial infections in pediatric intensive care units. VAP prolongs the treatment period of the patient in the healthcare institution, and therefore the mortality rates and the incidence of the disease increase. This causes both labor loss and damage to the national economy. Aim: In this study, it was aimed to evaluate the relationship between job satisfaction and knowledge level of nurses working in pediatric intensive care units to prevent ventilator-associated pneumonia. Method: It is a cross-sectional and descriptive study. The data were collected using the “Socio-demographic Question Form”,“Question Form for Preventing Ventilator-Associated Pneumonia ”and“ Minnesota Job Satisfaction Scale ”. SPSS program was used to analyze the data obtained in the study. For statistical calculations, t test, chi-square, frequency analysis were used in independent groups. Statistical significance level was taken as p <0.05. Finding: There was no significance between the correct answers given by the nurses to the questions about VAP Prevention and their job satisfaction. However, nurses’ correct response rates and job satisfaction were found to be quite high. Result: It was determined that which nurses mostly answered correctly to questions prepared to prevent ventilator-associated pneumonia and there was no significant relationship between job satisfaction and nurses’ knowledge levels.